2009
DOI: 10.1080/03235400600999422
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of entomopathogenic nematodes and an egg parasitoid for suppression of corn borers in Egypt

Abstract: Two entomopathogenic nematodes (EPNs) and an egg parasitoid for controlling three corn borers (Sesamia cretica, Chilo agamemnon and Ostrinia nubilalis) in corn fields. EPNs, Heterorhabditis bacteriophora (BA1) and Steinernema carpocapsae (BA2) were applied to the control S. cretica (after 40 d post planting) on different planting dates. Three releases of Trichogramma evanescens were also conducted at two-week intervals to control C. agamemnon and O. nubilalis starting at tasseling time for the three planting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The use of natural enemy agents in combination with selected insecticides, which have no effect on them, is effective in depressing the population density of the pest. Generally, egg parasitoids such as Trichogramma have been widely used as biological control agent as reported by Hassan (1982), Bigler (1984) and El-Wakeil & Hussein (2009); who confirmed that 65 -93% reduction in larval infestations of Ostrinia nubilalis in corn fields was achieved following Trichogramma releases in Germany and Switzerland as well in Egypt.…”
Section: Side Effects On Parasitoid Waspsmentioning
confidence: 87%
“…The use of natural enemy agents in combination with selected insecticides, which have no effect on them, is effective in depressing the population density of the pest. Generally, egg parasitoids such as Trichogramma have been widely used as biological control agent as reported by Hassan (1982), Bigler (1984) and El-Wakeil & Hussein (2009); who confirmed that 65 -93% reduction in larval infestations of Ostrinia nubilalis in corn fields was achieved following Trichogramma releases in Germany and Switzerland as well in Egypt.…”
Section: Side Effects On Parasitoid Waspsmentioning
confidence: 87%
“…Timing, rate and frequency of release are determined according to the nature of the target pests, natural enemies and crops. Pathogens like entompathogenic nematodes could be applied as sprays or injection [22,106,107]. Examples of cases of NE field releasing are summarized in Table 3.…”
Section: Release Of Natural Enemiesmentioning
confidence: 99%
“…The infested plants S. cretica were sprayed one time with 500 and 1000 IJs/ml of Steinernema carpocapsae and Heterorhabditis bacteriophora. Three releases of T. evanescens were conducted to control C. agamemnon and O. nubilalis [22].…”
Section: Combination Entomopathogenic Nematodes (Epns) and Egg Parasimentioning
confidence: 99%
See 1 more Smart Citation
“…The Entomopathogenic nematodes (EPNs) from the genera Heterorhabditis and Steinernema are obligate lethal parasites of insects and are globally used as safe biocontrol agents against wide range of insect pests (Hussein & El-Mahdi, 2019;Hussein et al, 2015;Nouh & Hussein, 2014;Saleh et al, 2009;El-Wakeil & Hussein, 2009;Ehlers, 2005;Burnell and Stock, 2000;). They occur in most agricultural soils all around the world (Hominick, 2002).…”
Section: Introductionmentioning
confidence: 99%